2005
DOI: 10.1158/1055-9965.epi-04-0812
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Distribution in Low-Grade Cervical Lesions: Comparison by Geographic Region and with Cervical Cancer

Abstract: Low-grade squamous intraepithelial lesions (LSIL) associated with certain human papillomavirus (HPV) genotypes may preferentially progress to cervical cancer. HPV genotyping may thus have the potential to improve the effectiveness of screening programs and to reduce overtreatment. LSIL cases (n = 8,308) from 55 published studies were included in a meta-analysis. HPV genotype distribution was assessed by geographic region and in comparison with published data on cervical squamous cell carcinoma (SCC). HPV detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

65
328
13
28

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(434 citation statements)
references
References 41 publications
65
328
13
28
Order By: Relevance
“…Although the high percentage of HR-HPV in LSIL coincides with the results of a meta-analysis carried out in different regions of the world 8 , there is no evidence of a statistically significant difference, thus suggesting that both LR-HPV and HR-HPV can be found in this lesion.…”
Section: Discussionsupporting
confidence: 78%
“…Although the high percentage of HR-HPV in LSIL coincides with the results of a meta-analysis carried out in different regions of the world 8 , there is no evidence of a statistically significant difference, thus suggesting that both LR-HPV and HR-HPV can be found in this lesion.…”
Section: Discussionsupporting
confidence: 78%
“…However, in the meta-analyses performed by Clifford et al (2003b), it is indicated that the five types, HPV 16,18,31,33 and 45, are the most predominant HPV types detected in high-grade cervical neoplasia and comprise almost 97% of the HPV DNA types detected in cervical carcinomas in Europe and Northern America. The number is compensated for multiple infections (Clifford et al, 2003b(Clifford et al, , 2005. There are also strong indications that the same five types are the most predominant ones in cervical carcinomas in the rest of the world (Munoz et al, 2004;Smith et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…HPV 16 and 18 are associated with an increased risk of progression to cervical neoplasia (Clifford et al, 2003(Clifford et al, , 2005b. However, the incidence of different HPV types in cervical cancers has been found to vary with different geographical populations (Bosch et al, 1995).…”
mentioning
confidence: 99%